High-temperature-resistant filter material, preparation method and filter bag

By adopting a three-layer structure high-temperature resistant filter material, combining thermoplastic resin and meta-aramid staple fiber, and adding antioxidants, the existing high-temperature resistant filter material is solved, and the problem of easy shrinkage and high cost in high temperature environments is achieved. High efficiency, stability, long life and low cost filtration.

CN119388856AInactive Publication Date: 2025-02-07JIANGSU AOKAI ENVIRONMENT TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411547916.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing high-temperature resistant filter materials are prone to shrink in high-temperature environments, resulting in blowing failure or severe thermal deterioration and high cost.

Method used

A high temperature resistant filter material is adopted in a three-layer structure consisting of a first heat-resistant fiber mesh filter layer, a second fabric reinforcement layer and a third heat-resistant fiber mesh non-filter layer, wherein the first heat-resistant fiber mesh filter layer contains a thermoplastic resin Made of staple fibers and metaara staple fibers, and add antioxidants.

Benefits of technology

It achieves the characteristics of not reducing heat resistance in high temperature environments, has high capture efficiency, good thermal stability, long service life and low production costs, and is suitable for asphalt, cement kiln, waste incineration, thermal power generation, steel and other fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant filtering material, a preparation method and a filtering bag, and relates to the technical field of filtering materials.The high-temperature-resistant filtering material at least comprises a three-layer structure composed of a first heat-resistant fiber net filtering layer, a second fabric reinforcing layer and a third heat-resistant fiber net non-filtering layer, the first heat-resistant fiber net filter layer comprises at least one short fiber made of thermoplastic resin and meta-aramid short fibers, 0.1 wt%-0.3 wt% of an antioxidant is added into the thermoplastic short fibers, the average fineness of the thermoplastic short fibers is 0.5 dtex-1. 5dtex, the melting point of the thermoplastic short fibers exceeds 250 DEG C, the crystallinity of the thermoplastic short fibers is 20%-50%, the content of terminal carboxyl-COOH of the thermoplastic short fibers is smaller than 8 eq / t, and the content of the meta-aramid short fibers is smaller than 8 eq / t. The average fineness of the meta-aramid short fibers is 1.5 dtex-3. 0 dtex, and the mixing ratio of the meta-aramid short fibers is 30 wt%-70 wt%. The filtering material disclosed by the invention has the characteristics of good high-temperature-resistant effect, high trapping efficiency, good thermal stability, long service life and low production cost, and can be applied to the fields of asphalt, cement kilns, waste incineration, thermal power generation, steel and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of filter materials, and in particular to a high temperature resistant filter material, a preparation method and a filter bag. Background Art

[0002] With the continuous development of the economy and the continuous improvement of people's living standards, people's requirements for the quality of the atmospheric environment are getting higher and higher, so the application of filter materials is becoming more and more extensive. In recent years, as the country actively promotes air pollution control, it has gradually improved the smoke emission standards of various industries. At present, bag filters are widely used in industries such as electricity, steel, cement, asphalt and waste incineration. In view of the complex environment on site, the filter materials used are also required to have high performance, generally requiring corrosion resistance, oxidation resistance, high temperature resistance, excellent mechanical properties, long service life, and stable structure. Generally speaking, filter bag manufacturers will use fiber raw materials with excellent high temperature resistance and chemical resistance to produce filter materials. Fibers made of general thermoplastic resins are often easy to shrink under high temperatures above 200°C, especially under the instantaneous highest temperature state, resulting in hoop bags, making the blowing ineffective, or the temperature exceeds the use limit of thermoplastic short fibers, resulting in serious thermal degradation and shortened life. When only aramid fibers are used, the final filter bag cost will be too high due to the cost of raw materials.

[0003] For example, Chinese patent CN106390623A discloses a method for preparing an aramid ultrafine fiber needle-punched filter bag, in which aramid fiber, glass fiber and polyphenylene sulfide are opened, mixed, combed and cross-laid to obtain the filter bag. Due to the presence of aramid ultrafine fiber, the filter bag can meet the stricter emission requirements, but no definition is made for the added polyphenylene sulfide, and the ultrafine aramid fiber is relatively expensive, so the filter bag finally has the disadvantages of high cost and easy shrinkage.

[0004] For example, Chinese patent CN202410389U discloses a high-temperature resistant needle-punched felt made of PPS fiber and aramid fiber, which has a high temperature resistance range of 160-190°C and an instantaneous working temperature of 190°C. The high temperature resistance is not high, and it cannot cope with the instantaneous working temperature of 220°C in asphalt mixing and steel industry. In addition, since the thickness of PPS fiber is not defined, it may lead to the defects of low capture efficiency and shortened service life. Summary of the invention

[0005] The purpose of the present invention is to solve the above technical problems and provide a high temperature resistant filter material, a preparation method and a filter bag.

[0006] In order to achieve the above technical objectives and meet the above technical requirements, the technical solution adopted by the present invention is: a high temperature resistant filter material, comprising at least a three-layer structure consisting of a first heat-resistant fiber mesh filter layer, a second fabric reinforcement layer and a third heat-resistant fiber mesh non-filter layer, the first heat-resistant fiber mesh filter layer comprising at least one short fiber made of a thermoplastic resin and an meta-aramid short fiber, the thermoplastic short fiber is added with 0.1wt%-0.3wt% antioxidant, the antioxidant comprises zinc borate and antimony oxide, the ratio of zinc borate to antimony oxide is 5:5-8:2, the average fineness of the thermoplastic short fiber is 0.5dtex-1.5dtex, the melting point exceeds 250°C, the crystallinity is 20-50%, the terminal carboxyl -COOH content of the thermoplastic short fiber is less than 8eq / t, the average fineness of the meta-aramid short fiber is 1.5dtex-3.0dtex, and the mixing ratio of the meta-aramid short fiber is 30wt%-70wt%.

[0007] Preferably: the thermoplastic staple fibers in the first heat-resistant fiber mesh filter layer are one or more of polyester resin PET, polyphenylene sulfide PPS, and nylon 66 fibers. The dry heat shrinkage of the thermoplastic staple fibers after treatment at 180°C for 30 minutes is 3-7%, and the weight average molecular weight Mw of the thermoplastic staple fibers is 30,000-60,000.

[0008] Preferably: the thermoplastic staple fibers in the first heat-resistant fiber mesh filter layer are preferably PPS fibers, with a crystallinity of 35-45%, a thermal shrinkage of 4-5.5%, and a terminal carboxyl -COOH content of less than 4eq / t.

[0009] Preferably, the second fabric reinforcement layer is preferably a fabric reinforcement layer made of meta-aramid staple fibers, with a gram weight of 80-200 g / m 2 The warp and weft peeling strengths of the reinforcing fabric, the upper fiber web and the lower fiber web are all greater than 300N / 5cm.

[0010] Preferably: the third heat-resistant fiber mesh non-filter layer includes meta-aramid staple fibers and thermoplastic staple fibers, the meta-aramid staple fibers account for greater than or equal to 40wt%, and the thermoplastic staple fibers are one or more of polyester resin PET, polyphenylene sulfide PPS, and nylon 66 fibers.

[0011] Preferably, the weight ratio of the first heat-resistant fiber mesh filter layer to the third heat-resistant fiber mesh non-filter layer is 4:6-7:3.

[0012] Preferably: the overall weight of the filter material is 400-650g / m 2 .

[0013] Preparation method of high temperature resistant filter material: different fibers are mixed by air flow stirring + stirring blade stirring, the air outlet holes are distributed between two stirring blades, the stirring blades are evenly distributed 2-5 pieces, and the number of air outlet holes is 1-3 times that of the stirring blades; the evenly mixed fibers are combed, laid, needled, shaped and calendered to obtain the filter material.

[0014] Filter bags made of high temperature resistant filter materials are used in asphalt, cement kilns, waste incineration, thermal power generation, steel and other fields.

[0015] Compared with the traditional structure, the beneficial effects of the present invention are as follows: short fibers made of thermoplastic resin and meta-aramid short fibers are used as the filter layer of the filter material, the short fibers made of thermoplastic resin are ultrafine fibers, and antioxidants are added. Compared with the filter material made of pure meta-aramid fibers, the prepared filter material does not decrease in high temperature resistance and has good heat resistance. It also has the characteristics of high capture efficiency, good thermal stability, long service life and low production cost, and can be used in asphalt, cement kilns, waste incineration, thermal power generation, steel and other fields. DETAILED DESCRIPTION

[0016] The present invention will be further described below.

[0017] A high temperature resistant filter material, comprising at least a three-layer structure consisting of a first heat-resistant fiber mesh filter layer, a second fabric reinforcement layer and a third heat-resistant fiber mesh non-filter layer, but not limited to a three-layer structure, the filter layer surface and the non-filter layer surface can also be impregnated with polytetrafluoroethylene PTFE or coated with polytetrafluoroethylene PTFE to increase its chemical resistance. Polytetrafluoroethylene PTFE coating can also be used but is not recommended. The heat-resistant fibers in the first heat-resistant fiber mesh are composed of a mixture of short fibers made of at least one thermoplastic resin and meta-aramid short fibers. The average fineness of thermoplastic staple fibers is 0.5dtex-1.5dtex. The purpose of using ultrafine thermoplastic staple fibers is to fill the ultrafine thermoplastic staple fibers into the gaps of meta-aramid staple fibers to improve the overall filtration performance of the filter material. The finer the fibers, the smaller the pores between the fibers, and the better the capture effect. However, when the fineness of thermoplastic staple fibers is less than 0.5dtex, it is difficult to produce the fibers because the fibers are too fine, or the cost will increase when produced by special composite spinning methods, and it is difficult to open and comb the fibers, so the filtration effect achieved is even worse than that of fibers above 0.5dtex. When the fineness of thermoplastic staple fibers is greater than 1.5dtex, the filtration effect is reduced due to the coarser fibers, and it cannot meet the current more stringent 10mg / Nm 3 The following emission standards, here the fiber is preferably 0.7 to 1.2 dtex.

[0018] The melting point of thermoplastic staple fibers exceeds 250°C and the crystallinity is 20-50%. These two indicators are related to the heat resistance of thermoplastic staple fibers. When the melting point is lower than 250°C, although it is mixed with meta-aramid staple fibers, the thermoplastic staple fibers are severely thermally degraded at high temperatures, or are in a semi-molten or molten state, making the filter material completely ineffective. When the crystallinity is less than 20%, the thermal stability of the fiber is poor and it is easy to shrink at high temperatures, causing hoop bags and loss of the blowing effect. When the crystallinity is greater than 50%, the softness of the fiber is affected, combing is difficult, and it is difficult to form a uniform cotton net, resulting in poor filtration performance of the filter material.

[0019] The average fineness of meta-aramid staple fibers is 1.5dtex-3.0dtex, and the mixing ratio of meta-aramid staple fibers is 30wt%-70wt%. When the average fineness of meta-aramid staple fibers is less than 1.5dtex, the production cost of the fibers increases, resulting in an increase in the cost of the final filter felt raw materials. When the fiber fineness is greater than 3.0dtex, the gaps between the fibers are larger, and the short fibers made of ultra-fine thermoplastic resin cannot be completely filled into the large gaps, resulting in reduced capture efficiency. When the mixing ratio of meta-aramid staple fibers is less than 30wt%, the heat resistance is reduced, and it cannot be used in high-temperature projects with instantaneous temperatures above 200°C and long-term use temperatures above 170°C. When the mixing ratio of meta-aramid staple fibers is greater than 70wt%, cost savings are not significant.

[0020] The terminal carboxyl -COOH content of thermoplastic staple fibers is less than 8eq / t, and the terminal carboxyl content greatly affects the heat resistance of thermoplastic staple fibers. Only by controlling the terminal carboxyl content within 8eq / t can the heat resistance of thermoplastic staple fibers approach or even reach the same level as meta-aramid.

[0021] The short fibers made of thermoplastic resin are added with 0.1wt%-0.3wt% antioxidant to improve the heat resistance of the thermoplastic fibers. The antioxidant is preferably added during the fiber manufacturing stage. The average diameter of the antioxidant particles is preferably less than or equal to 500nm. The particles with an average particle diameter less than 500nm are uniformly mixed with the plastic resin and then melt-spun.

[0022] The high temperature resistant filter material, the thermoplastic short fibers in the first heat resistant fiber mesh filter layer can be one or more of PET, PPS, and nylon 66 fibers. As the heat resistance of the thermoplastic fibers increases, the mixing ratio of the thermoplastic fibers can be gradually increased. The dry heat shrinkage of the fibers after treatment at 180°C for 30 minutes is 3-7%. When the dry heat shrinkage is greater than 7%, the filter felt prepared is easy to shrink at high temperatures, causing hoop bags. When the dry heat shrinkage is less than 3%, it means that the crystallinity is too high, the fibers are too hard, and combing is difficult, resulting in poor uniformity of the cotton mesh and low filtering performance. The weight average molecular weight Mw of the thermoplastic short fibers is 30,000-60,000. If the weight average molecular weight is too small, it will affect the overall strength. If the weight average molecular weight is too high, the fibers made will feel too hard, resulting in poor combing and affecting the filtering performance of the final filter material.

[0023] The thermoplastic short fibers in the first heat-resistant fiber mesh filter layer of the high-temperature resistant filter material are preferably PPS fibers, and the crystallinity is preferably 35-45%, and the thermal shrinkage is preferably 4-5.5%. The crystallinity of the fiber is closely related to the thermal shrinkage of the fiber itself. The higher the crystallinity, the better its stability in a heated environment. When the fiber crystallinity is greater than 35%, the fiber has a dry heat shrinkage of less than 5.5% after heat treatment at 180°C for 30 minutes, and the filter felt produced by the fiber is more stable. When the fiber crystallinity is less than 45%, the flexibility of the fiber is within the optimal range, and at this time it has the characteristics of small thermal shrinkage and flexibility.

[0024] The short fibers made of thermoplastic resin are added with 0.1wt%-0.3wt% antioxidant. Too little antioxidant will not work, and too much antioxidant will affect the fiber strength. The antioxidant contains zinc borate and antimony oxide at the same time. The ratio of zinc borate to antimony oxide is 5:5-8:2. When zinc borate and antimony oxide are added at the same time, the heat resistance of thermoplastic fiber is the best, and the heat resistance of PET can even be improved to a level close to that of meta-aramid. When the proportion of antimony oxide is greater than 50%, the influence on the strength of the fiber increases, and the strength begins to decrease significantly. When the proportion of antimony oxide is less than 20%, the heat resistance is not significantly improved.

[0025] The terminal carboxyl -COOH content of the thermoplastic staple fiber is preferably less than 4eq / t. The smaller the carboxyl content, the better the heat resistance. When it is less than 4eq / t, the heat resistance is equal to or even exceeds that of meta-aramid.

[0026] The second fabric reinforcement layer of the high temperature resistant filter material is preferably a fabric reinforcement layer made of meta-aramid short fibers, and its gram weight is 80-200g / m 2The heat resistance temperature of meta-aramid reaches 220℃. After using meta-aramid as the base fabric of the filter felt, the strength retention rate of the filter felt at high temperature is higher and the service life is longer. In addition to meta-aramid, PPS and PTFE fiber materials can also be used as raw materials for the base fabric. When the base fabric weight is less than 80g / m 2 When the overall strength of the base fabric is low, it is often difficult to meet the radial 900N / 5cm requirement. When the base fabric weight is higher than 200g / m 2 When the radial strength is too high, the cost is increased and waste is caused, and the weight of the first heat-resistant fiber mesh layer and the third heat-resistant fiber mesh layer is relatively reduced, which affects the filtering effect and the weft strength. The warp and weft peeling strength of the reinforcing fabric, the upper fiber mesh and the lower fiber mesh are all greater than 300N / 5cm. The needle density during acupuncture has an impact on the peeling strength. If the needle density is insufficient, the peeling strength is insufficient.

[0027] The third heat-resistant fiber net non-filtering layer of the high-temperature resistant filter material is composed of meta-aramid short fibers, which account for more than or equal to 40wt%. A thermoplastic short fiber can also be added to the third heat-resistant fiber net non-filtering layer. The thermoplastic short fiber can be one or more of PET, PPS, and nylon 66 fibers. The third heat-resistant fiber net can be 100% aramid fiber, and an appropriate amount of thermoplastic short fiber can also be added. The proportion of thermoplastic short fiber that can be added is proportional to its heat resistance. The proportion of thermoplastic short fibers with relatively poor heat resistance such as PET and nylon 66 is preferably less than or equal to 30wt%, and the proportion of thermoplastic short fibers with relatively good heat resistance such as PPS is preferably less than or equal to 60wt%. When mixing the two fibers, attention should be paid to the uniformity of the mixing. The higher the uniformity, the better.

[0028] The weight ratio of the first heat-resistant fiber mesh filter layer and the third heat-resistant fiber mesh non-filter layer of the high-temperature resistant filter material is 4:6-7:3. The first heat-resistant fiber mesh filter layer is closely related to the overall filtering performance of the filter felt. When the first heat-resistant fiber mesh filter layer accounts for less than 40%, the gram weight is too small, resulting in reduced filtering effect. When the first heat-resistant fiber mesh filter layer accounts for more than 70%, the non-filter layer gram weight is too small. During the long-term friction with the keel, the base fabric is often more easily exposed, resulting in a decrease in strength and a shortened service life.

[0029] The overall weight of the high temperature resistant filter material is 400-650g / m 2 The gram weight is related to the filtering performance and strength of the filter material. When the overall gram weight of the filter material is less than 400g / m 2 When the collection efficiency decreases, it is difficult to ensure 10mg / Nm 3The following discharge, and its weft strength will also decrease, it is difficult to ensure that the weft strength can exceed 1200N / 5cm. Increasing the gram weight can effectively improve the filtering effect, but when the gram weight rises to 650g / m 2 When the weight is above 450g-600g / m2, the influence on the filtration effect can be ignored, and the cost of the filter material will be increased, resulting in unnecessary waste. 2 .

[0030] Preparation method of high temperature resistant filter material: When mixing different fibers, air flow stirring + stirring blade stirring is adopted, and the air outlet holes are distributed between two stirring blades. The stirring blades are evenly distributed 2-5 pieces, and the number of air outlet holes is 1-3 times that of the stirring blades. This design is different from the previous cotton mixing machine, which is conducive to the full and uniform mixing of different fibers in a short time. The mixing uniformity is better than other mixing methods on the market. The mixing time needs to be controlled at more than 3 minutes. The evenly mixed fibers are obtained through the steps of combing, web laying, needle punching, shaping and calendering to obtain the filter material.

[0031] A filter bag can be made from this high temperature resistant filter material. When making filter bags, it should be noted that if the emission requirement is less than 5mg / Nm 3 , special processing is required at the seams, such as thermal bonding, or sealing the seams with heat-resistant glue.

[0032] This type of filter bag is used in asphalt, cement kilns, waste incineration, thermal power generation, steel and other fields.

[0033] The present invention is described in more detail by the following examples and comparative examples. The testing methods for the various properties of the filter material of the present invention are as follows, but the testing methods are not limited thereto.

[0034]

Carboxyl terminal group

[0035]

Average fiber fineness

[0036]

Content of polyphenylene sulfide fiber

[0037]

Weight

[0038]

Crystallinity

[0039]

Melting point

[0040] Example 1: 35wt% of polyester staple fibers with an average fineness of 0.8dtex and 65wt% of meta-aramid staple fibers with an average fineness of 2.2dtex were mixed in a three-blade three-air outlet stirring device for 6 minutes, fully mixed and evenly mixed, and then opened, combed and laid to obtain a filter layer, wherein the melting point of polyester is 255°C, the crystallinity is 37%, the carboxyl terminal group content is 7eq / t, the weight-average molecular weight Mw is 35000, and the dry heat shrinkage rate after treatment at 180°C for 30 minutes is 6.0%; the addition ratio of zinc borate and antimony oxide mixture is 0.2%, and the ratio of zinc borate: antimony oxide is 6:4; the meta-aramid staple fibers with an average fineness of 2.2dtex are opened, combed and laid to obtain a non-filter layer; wherein the weight ratio of the filter layer to the non-filter layer is 5:5. The yarn made of meta-aramid staple fibers is made by weaving to obtain a yarn with a gram weight of 120g / m 2 After stacking in the order of filter layer, base fabric, and non-filter layer, needle punching and heat setting are performed, the overall weight of the filter felt obtained is 500g / m 2, use this filter felt to make filter bags, and seal the middle seam with glue after the filter bags are sewn. This filter bag can be used in high-temperature fields such as asphalt, cement kilns, waste incineration, thermal power generation, etc., and can reach 10mg / Nm under the condition that the filtering wind speed is less than or equal to 1.0m / min 3 After being used for 3 years at an instantaneous temperature of 220°C and a long-term use temperature of 180°C, its strength retention rate is still as high as over 80%.

[0041] Example 2: 50wt% of PPS polyphenylene sulfide staple fibers with an average fineness of 0.9dtex and 50wt% of meta-aramid staple fibers with an average fineness of 2.2dtex were mixed in a three-blade three-air outlet stirring device for 6 minutes, fully mixed and evenly mixed, and then loosened, combed and laid to obtain a filter layer, wherein the melting point of PPS polyphenylene sulfide is 282°C, the crystallinity is 40%, the carboxyl terminal group content is 7eq / t, the weight-average molecular weight Mw is 50,000, and the dry heat shrinkage rate after treatment at 180°C for 30 minutes is 4.3%; the addition ratio of the mixture of zinc borate and antimony oxide is 0.2%, and the ratio of zinc borate to antimony oxide is 6:4; the meta-aramid staple fibers with an average fineness of 2.2dtex are opened, combed and laid to obtain a non-filter layer; wherein the weight ratio of the filter layer to the non-filter layer is 6:4. The yarn made of meta-aramid staple fibers is made by weaving to obtain a yarn with a gram weight of 120g / m 2 After stacking in the order of filter layer, base fabric, and non-filter layer, needle punching and heat setting are performed, the overall weight of the filter felt obtained is 550g / m 2 , use this filter felt to make filter bags, and use glue to seal the middle seam after the filter bags are sewn. This filter bag can be used in high-temperature fields such as asphalt, cement kilns, and garbage incineration, and can reach 5mg / Nm under the condition that the filtering wind speed is less than or equal to 1.0m / min 3 After being used for 3 years at an instantaneous temperature of 220°C and a use temperature of 200°C, its strength retention rate is still as high as over 80%.

[0042] Example 3: 50wt% of PPS staple fibers with an average fineness of 0.9dtex and 50wt% of meta-aramid staple fibers with an average fineness of 2.2dtex were mixed in a three-blade three-air outlet stirring device through a cotton mixer for 6 minutes, and the mixture was fully and evenly mixed, and then loosened, combed and laid to obtain a filter layer, wherein the melting point of PPS is 282°C, the crystallinity is 40%, the carboxyl terminal group content is 2eq / t, the weight-average molecular weight Mw is 50,000, and the dry heat shrinkage rate after treatment at 180°C for 30 minutes is 4.3%; the addition ratio of the mixture of zinc borate and antimony oxide is 0.2%, and the ratio of zinc borate to antimony oxide is 7:3; the meta-aramid staple fibers with an average fineness of 2.2dtex were opened, combed and laid to obtain a non-filter layer; wherein the weight ratio of the filter layer to the non-filter layer is 6:4. The yarn made of meta-aramid staple fibers was made by weaving to obtain a yarn with a gram weight of 120g / m 2 After stacking in the order of filter layer, base fabric, and non-filter layer, needle punching and heat setting are performed, the overall weight of the filter felt obtained is 550g / m 2 , use this filter felt to make filter bags, and use glue to seal the middle seam after the filter bags are sewn. This filter bag can be used in high-temperature fields such as asphalt, cement kilns, and garbage incineration, and can reach 5mg / Nm under the condition that the filtering wind speed is less than or equal to 1.0m / min 3 After 3 years of use at an instantaneous temperature of 220°C and a use temperature of 200°C, its strength retention rate is still as high as over 90%.

[0043] Example 4: 35wt% of nylon 66 staple fibers with an average fineness of 0.6dtex and 65wt% of meta-aramid staple fibers with an average fineness of 2.2dtex were mixed in a three-blade three-air outlet stirring device for 6 minutes, fully mixed and evenly mixed, and then loosened, combed and laid to obtain a filter layer, wherein the melting point of nylon 66 is 252°C, the crystallinity is 43%, the carboxyl terminal group content is 7eq / t, the weight-average molecular weight Mw is 42000, and the dry heat shrinkage rate after treatment at 180°C for 30 minutes is 4.7%; the addition ratio of zinc borate and antimony oxide mixture is 0.2%, and the ratio of zinc borate: antimony oxide is 6:4; the meta-aramid staple fibers with an average fineness of 2.2dtex are opened, combed and laid to obtain a non-filter layer; wherein the weight ratio of the filter layer to the non-filter layer is 5:5. The yarn made of meta-aramid is woven to obtain a 120g / m 2 After stacking in the order of filter layer, base fabric, and non-filter layer, needle punching and heat setting are performed, the overall weight of the filter felt is 550g / m 2, use this filter felt to make filter bags, and use glue to seal the middle seam after the filter bags are sewn. This filter bag can be used in high-temperature fields such as asphalt, cement kilns, waste incineration, thermal power generation, etc., and can reach 5mg / Nm under the condition that the filtering wind speed is less than or equal to 1.0m / min 3 After being used for 3 years at an instantaneous temperature of 220°C and a long-term use temperature of 180°C, its strength retention rate is still as high as over 85%.

[0044] Example 5: 50wt% of PPS staple fibers with an average fineness of 0.9dtex and 50wt% of meta-aramid staple fibers with an average fineness of 1.5dtex were mixed in a three-blade six-air outlet stirring device through a cotton mixer for 5 minutes, and the mixture was fully and evenly mixed, and then loosened, combed and laid to obtain a filter layer; wherein the melting point of PPS is 282°C, the crystallinity is 40%, the carboxyl terminal group content is 2eq / t, the weight-average molecular weight Mw is 50,000, and the dry heat shrinkage rate after treatment at 180°C for 30 minutes is 4.3%; the addition ratio of the mixture of zinc borate and antimony oxide is 0.2%, and the ratio of zinc borate to antimony oxide is 7:3; the meta-aramid staple fibers with an average fineness of 2.2dtex were opened, combed and laid to obtain a non-filter layer; wherein the weight ratio of the filter layer to the non-filter layer is 6:4. The yarn made of meta-aramid was made by weaving to obtain a 120g / m 2 The filter layer, base fabric and non-filter layer are stacked in the order of needle punching and heat setting. The overall weight of the filter felt is 550g / m 2 , use this filter felt to make filter bags, and seal the middle seam with glue after the filter bags are sewn. This filter bag can be used in high-temperature fields such as asphalt, cement kilns, and garbage incineration, and can reach 3mg / Nm under the condition that the filtering wind speed is less than or equal to 0.7m / min. 3 After 3 years of use at an instantaneous temperature of 220°C and a use temperature of 200°C, its strength retention rate is still as high as over 90%.

[0045] Example 6: 70 wt% of PPS staple fibers with an average fineness of 0.9 dtex and 30 wt% of meta-aramid staple fibers with an average fineness of 2.2 dtex were mixed in a three-paddle three-air outlet stirring device for 6 minutes by a cotton mixer, fully mixed and evenly mixed, and then opened, combed and laid to obtain a filter layer, wherein the melting point of PPS is 282°C, the crystallinity is 40%, the carboxyl terminal group content is 2eq / t, the weight average molecular weight Mw is 50000, and treated at 180°C for 30 minutes The dry heat shrinkage rate is 4.3%; the addition ratio of zinc borate and antimony oxide mixture is 0.2%, and the ratio of zinc borate: antimony oxide is 7:3; 50% of the average fineness of 2.2dtex meta-aramid staple fibers and 50% of the average fineness of 2.2dtex PPS staple fibers, and other properties of the fibers are the same as the 0.9dtexPPS disclosed in this embodiment, are uniformly mixed, loosened, combed and laid to obtain a non-filter layer, wherein the weight ratio of the filter layer to the non-filter layer is 6:4. The yarn made of meta-aramid staple fibers is made by weaving to obtain a gram weight of 120g / m 2 The filter layer, base fabric and non-filter layer are stacked in the order of needle punching and heat setting. The filter felt has an overall gram weight of 550g / m 2 , use this filter felt to make filter bags, and use glue to seal the middle seam after the filter bags are sewn. This filter bag can be used in high-temperature fields such as asphalt, cement kilns, and garbage incineration, and can reach 5mg / Nm under the condition that the filtering wind speed is less than or equal to 1.0m / min 3 After being used for 3 years at an instantaneous temperature of 220°C and a use temperature of 200°C, its strength retention rate is still as high as over 88%.

[0046] Embodiment 7: other conditions are the same as those of embodiment 2. The cotton mixer is mixed in a two-stirring blade and two-air outlet stirring device for 8 minutes. The mixture is fully and evenly mixed. After the number of stirring blades and stirring air holes is reduced, the stirring time needs to be appropriately increased.

[0047] Example 8: Other conditions are the same as those in Example 2. The cotton mixer is mixed in a five-stirring blade and ten-air hole stirring device for 9 minutes to fully and evenly mix the mixture. When there are too many stirring blades and stirring air holes, the stirring blades are spaced too small, and the stirring air holes distribute a small amount of airflow, so that the spacing cannot be fully circulated, and the fibers cannot be fully mixed. It is also necessary to appropriately increase the stirring time.

[0048] Comparative Example 1: The meta-aramid staple fibers with an average fineness of 1.0 dtex were opened, carded and laid to obtain a filter layer; the meta-aramid staple fibers with an average fineness of 2.2 dtex were opened, carded and laid to obtain a non-filter layer; the weight ratio of the filter layer to the non-filter layer was 5:5. The yarn made of meta-aramid was woven to obtain a yarn with a grammage of 120 g / m 2 The filter layer, base fabric and non-filter layer are stacked in the order of needle punching and heat setting. The filter felt has an overall weight of 500 g / m 2 , use this filter felt to make filter bags, and seal the middle seam with glue after the filter bags are sewn. This filter bag can be used in high-temperature fields such as asphalt, cement kilns, waste incineration, thermal power generation, etc., and can reach 10mg / Nm under the condition that the filtering wind speed is less than or equal to 1.0m / min 3 The emission is within 200℃. After 3 years of use at an instantaneous temperature of 220℃ and a use temperature of 200℃, its strength retention rate is still as high as over 85%. However, the material cost of this case has increased by at least 10%.

[0049] Comparative Example 2: 50wt% of polyester staple fibers with an average fineness of 0.8dtex and 50wt% of meta-aramid staple fibers with an average fineness of 2.2dtex were mixed in a three-blade three-air outlet stirring device for 6 minutes, and after being fully mixed, they were loosened, combed and laid to obtain a filter layer, wherein the melting point of polyester was 255°C, the crystallinity was 37%, the carboxyl terminal group content was 20eq / t, the weight-average molecular weight Mw was 35000, and the dry heat shrinkage rate after treatment at 180°C for 30 minutes was 6.0%; the addition ratio of the mixture of zinc borate and antimony oxide was 0.2%, and the ratio of zinc borate to antimony oxide was 6:4. Meta-aramid staple fibers with an average fineness of 2.2dtex were opened, combed and laid to obtain a non-filter layer; wherein the weight ratio of the filter layer to the non-filter layer was 5:5. The yarn made of meta-aramid was made by weaving a yarn with a gram weight of 120g / m 2 The filter layer, base fabric and non-filter layer are stacked in the order of needle punching and heat setting. The filter felt has an overall weight of 500 g / m 2 , use this filter felt to make filter bags, and use glue to seal the middle seam after the filter bags are sewn. This filter bag can be used in high-temperature fields such as asphalt, cement kilns, waste incineration, thermal power generation, etc., and can reach 5mg / Nm under the condition that the filtering wind speed is less than or equal to 1.Om / min. 3 The strength retention rate is 50% after using it for 6 months under the conditions of instantaneous temperature of 220℃ and operating temperature of 180℃. After 6 months, the filter bag is damaged due to the decrease of strength and cannot be used any more.

[0050] Comparative Example 3: 50wt% of PPS staple fibers with an average fineness of 0.9dtex and 50wt% of meta-aramid staple fibers with an average fineness of 2.2dtex were mixed in a three-blade three-air outlet stirring device through a cotton mixer for 6 minutes. After being fully mixed, they were loosened, combed and laid to obtain a filter layer, wherein the melting point of PPS was 282°C, the crystallinity was 40%, the carboxyl terminal group content was 2eq / t, the weight-average molecular weight Mw was 50,000, and the dry heat shrinkage rate after treatment at 180°C for 30 minutes was 4.3%. No antioxidant was added; the meta-aramid staple fibers with an average fineness of 2.2dtex were loosened, combed and laid to obtain a non-filter layer, wherein the weight ratio of the filter layer to the non-filter layer was 6:4. The yarn made of meta-aramid was woven to obtain a 120g / m 2 The filter layer, base fabric and non-filter layer are stacked in the order of needle punching and heat setting. The overall weight of the filter felt is 550g / m 2 , use this filter felt to make filter bags, and use glue to seal the middle seam after the filter bags are sewn. This filter bag can be used in high-temperature fields such as asphalt, cement kilns, and garbage incineration, and can reach 5mg / Nm under the condition that the filtering wind speed is less than or equal to 1.m / min 3 When used for 2 years at an instantaneous temperature of 220°C and a use temperature of 190°C, the strength retention rate is less than 60%.

[0051] Comparative Example 4: Other conditions are completely the same as those in Comparative Example 3. No blades are used for mixing, and only air flow is used for mixing for 6 minutes. The obtained filter material can only absorb 15mg / Nm 3 emission requirements.

[0052] Comparative Example 5: 50wt% of PPS staple fibers with an average fineness of 1.4dtex and 50wt% of meta-aramid staple fibers with an average fineness of 2.2dtex were mixed in a cotton blender, opened, combed and laid to obtain a filter layer, wherein the melting point of PPS is 280°C, the crystallinity is 12%, and the dry heat shrinkage rate after treatment at 180°C for 30 minutes is 25%; the meta-aramid staple fibers with an average fineness of 2.2dtex were opened, combed and laid to obtain a non-filter layer; wherein the weight ratio of the filter layer to the non-filter layer is 6:4. The yarn made of meta-aramid was woven to obtain a 120g / m 2 The base fabric layer of this filter felt begins to shrink significantly when the temperature exceeds 130°C and cannot be used in high temperature areas.

[0053] The above embodiments of the present invention are merely examples to clearly illustrate the present invention, but are not intended to limit the protection scope of the present invention. All equivalent technical solutions also belong to the scope of the present invention. The patent protection scope of the present invention should be defined by the claims.

Claims

1. A high temperature resistant filter material, characterized in that: The invention comprises at least a three-layer structure consisting of a first heat-resistant fiber mesh filter layer, a second fabric reinforcement layer and a third heat-resistant fiber mesh non-filter layer, wherein the first heat-resistant fiber mesh filter layer comprises at least one short fiber made of a thermoplastic resin and an meta-aramid short fiber, the thermoplastic short fiber is added with 0.1wt%-0.3wt% antioxidant, the antioxidant comprises zinc borate and antimony oxide, the ratio of zinc borate to antimony oxide is 5:5-8:2, the average fineness of the thermoplastic short fiber is 0.5dtex-1.5dtex, the melting point exceeds 250°C, the crystallinity is 20-50%, the terminal carboxyl -COOH content of the thermoplastic short fiber is less than 8eq / t, the average fineness of the meta-aramid short fiber is 1.5dtex-3.0dtex, and the mixing ratio of the meta-aramid short fiber is 30wt%-70wt%.

2. The high temperature resistant filter material according to claim 1, characterized in that: The thermoplastic staple fibers in the first heat-resistant fiber mesh filter layer are one or more of PET, PPS, and nylon 66 fibers. The dry heat shrinkage of the thermoplastic staple fibers after treatment at 180°C for 30 minutes is 3-7%, and the weight average molecular weight Mw of the thermoplastic staple fibers is 30,000-60,000.

3. The high temperature resistant filter material according to claim 1 or 2, characterized in that: The thermoplastic short fibers in the first heat-resistant fiber mesh filter layer are preferably PPS fibers, with a crystallinity of 35-45%, a thermal shrinkage of 4-5.5%, and a terminal carboxyl group -COOH content of the thermoplastic short fibers of less than 4eq / t.

4. The high temperature resistant filter material according to claim 1, characterized in that: The second fabric reinforcement layer is preferably a fabric reinforcement layer made of meta-aramid staple fibers, and its gram weight is 80-200 g / m 2 The warp and weft peeling strengths of the reinforcing fabric, the upper fiber web and the lower fiber web are all greater than 300N / 5cm.

5. The high temperature resistant filter material according to claim 1, characterized in that: The third heat-resistant fiber mesh non-filter layer includes meta-aramid staple fibers and thermoplastic staple fibers, wherein the meta-aramid staple fibers account for greater than or equal to 40wt%, and the thermoplastic staple fibers are one or more of PET, PPS, and nylon 66 fibers.

6. The high temperature resistant filter material according to claim 1, characterized in that: The weight ratio of the first heat-resistant fiber mesh filter layer and the third heat-resistant fiber mesh non-filter layer is 4:6-7:

3.

7. The high temperature resistant filter material according to claim 1, characterized in that: The overall weight of the filter material is 400-650g / m 2 .

8. The method for preparing a high temperature resistant filter material according to claim 1, characterized in that: Different fibers are mixed by air flow stirring + stirring blade stirring. The air outlet holes are distributed between two stirring blades. There are 2-5 stirring blades evenly distributed, and the number of air outlet holes is 1-3 times that of the stirring blades. The evenly mixed fibers are combed, laid, needled, shaped and calendered to obtain the filter material.

9. A filter bag, characterized in that: Made from the high temperature resistant filter material described in any one of claims 1 to 8.

10. A filter bag according to claim 9, characterized in that: The filter bag is used in asphalt, cement kiln, garbage incineration, thermal power generation, and steel fields.

Citation Information

Patent Citations

  • Preparation method of aramid superfine fiber needled filter bag

    CN106390623A

  • PPS fiber and aramid fiber composite high-temperature resisting needled-punched felt

    CN202410389U

  • High-temperature-resistant organic friction lining of automobile brake and manufacturing method of friction lining

    CN105351413A

  • High-temperature-resistant filtering material

    CN112973284A

  • High-temperature-resistant filtering material for ultralow emission

    CN113304546A